Impact of CSR Innovation Policy on Sustainable Development - Kumar, Rajiv; Sinha, Kunal (Integrated Journal for Research in Arts and Humanities, 2024)
Corporate Social Responsibility (CSR) innovation policy has become a pivotal feature of modern industry, integrating social, environmental, and economic responsibilities into corporate strategies. This paper explores multifaceted role of CSR innovation in enhancing company reputation, driving sustainable development, fostering innovation, ensuring compliance, and improving risk management. Additionally, it highlights how CSR practices attract and retain talent, deliver economic benefits, and strengthen stakeholder relations. By setting industry standards and encouraging collaboration, CSR policies not only benefit individual companies but also contribute to broader societal and environmental goals. Through case studies of companies like Unilever, Tesla, and Patagonia, this paper demonstrates the tangible impacts of CSR innovation on industry performance and sustainability. Overall, CSR innovation policy is essential for achieving long-term profitability, competitive advantage, and ethical stewardship in the corporate world.